Thermal and hydraulic characteristics of turbulent nanofluids flow in trapezoidal-corrugated channel: Symmetry and zigzag shaped - Ajeel, Raheem K.; W. Salim, W.S-I.; Hasnan, Khalid (Elsevier, 2018)
Thermal and hydraulic characteristics of turbulent nanofluids flow in a trapezoidal-corrugated channel are numerically investigated by implementing the finite volume method to solve the governing equations. The adiabatic condition for the straight walls, constant heat flux for the corrugated walls, and two configurations of trapezoidal channel symmetry and zigzag shape were examined. The performance of a trapezoidal-corrugated channel with four different kinds of nanofluids ( ZnO, Al2O3, CuO, and SiO2), with four various nanoparticle volume fractions of 2%, 4%, 6% and 8% using water as base fluid is thoroughly analyzed and discussed. The nanoparticles diameter, another parameter is taken into consideration, varied from 20 to 80 nm. Results show that the symmetry profile of trapezoidal-corrugated channel has a great effect on the thermal performance compared with a straight profile and zigzag profile. The Nusselt number dropped as the nanoparticle diameter grew; however, it grew as the nanoparticle volume fraction and Reynolds number dropped. The best improvement in heat transfer among the nanofluids types was by SiO2-water. The present investigation uncovers that these trapezoidal symmetry-corrugated channels have favorable circumstances by utilizing nanofluids and in this manner fill in as a promising contender for incorporation in more compact heat exchanger devices.